Liver Disease and Central Nervous System Dysfunction: Linking the Two - A Narrative Review - Maciej Tenderenda; Bartosz Buczkowski; Piotr Oleksy; Agnieszka Klecza; Aleksandra Broniak; Magdalena Reclik; Karol Zieliński; Aarushi Chourasia; Krzysztof Nowakowski; Martyna Chraścina (Journal of Education, Health and Sport)
Introduction: Liver dysfunction can significantly impact the central nervous system (CNS), leading to neuropsychiatric complications such as hepatic encephalopathy (HE). HE, a potentially reversible condition, results from the accumulation of toxins, particularly ammonia, which a diseased liver fails to detoxify, affecting brain function. It is commonly associated with chronic liver diseases like cirrhosis but can also occur acutely in cases of fulminant liver failure.